Biochemical responses of hairgrass (Deschampsia caespitosa) to hydrological change - Luo, Qiaoyu; Ma, Yonggui; Chen, Zhi; Xie, Huichun; Wang, Yanlong; Zhou, Lianyu; Ma, Yushou (Frontiers in Plant Science, 2022)
Plant growth and development are closely related to water availability, whereas water deficit and water excess are detrimental to plants, causing a series of damage to plant morphology, cell structure, physiological and biochemical processes. In the long evolutionary process, plants have evolved a series of complex mechanisms, including alterations in morphological structure as well as physiological and biochemical processes to combat against stressful conditions. We evaluated differences in ascorbic acid (AsA) and glutathione (GSH) contents and activities of enzymes involved in the AsA-GSH cycle in hairgrass under contrasting hydrological regimes during 28 days stress duration at a week interval in a pot trial using a complete random block design. The treatments were as follows: 1) heavily water-logging, 2) moderate water-logging, 3) light water-logging, 4) light drought, 5) moderate drought, 6) heavily drought, and 7) a control (CK) with moderate water availability to meet the requirement of plant growth. Results revealed that hairgrass subjected to water stress can stimulate enzymatic activities of ascorbate peroxidase, glutathione peroxidase, glutathione reductase, dehydroascorbate reductase, monodehydroascorbate reductase and L-galactono-1,4-lactone dehydrogenase, switched on the ascorbate-glutathione (AsA-GSH) cycle and the L-galactose synthesis, up-regulated the contents of AsA and GSH, and maintained higher ratios of reduced to oxidized ascorbate (AsA/DHA) and reduced to oxidized glutathione (GSH/GSSG) to reduce potential oxidative damage. However, the hairgrass under light waterlogging stress did not switch on the AsA-GSH pathway. In general, the critic substances and enzyme activities in AsA-GSH metabolic pathway increased as the increase of water stress intensity. As the increase of exposure duration, the critic antioxidant substances content and enzyme activities increased first and then maintained a relatively stable higher level. Our findings provide comprehensive information on physiological responses of hairgrass to hydrological change, which would be a major step for accelerating ecological restoration of degradation alpine wetlands in the Qinghai-Tibetan Plateau.